2011
DOI: 10.1016/j.jcmg.2011.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis in Ancient Egyptian Mummies

Abstract: Atherosclerosis is commonplace in mummified ancient Egyptians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 130 publications
(77 citation statements)
references
References 23 publications
(16 reference statements)
2
68
0
7
Order By: Relevance
“…In recent studies, this condition has been the subject of investigation in mummified remains. In particular, to assess whether atherosclerosis was a condition dependent on the lifestyle of Egyptian elites or if it was also encountered in ancient populations with different subsistence strategies (Allam et al, 2009(Allam et al, , 2011Thompson et al, 2013). Studies have demonstrated atherosclerosis in other prehistoric and historic mummies, including the chalcolithic Iceman, a mummy from the Joseon dynasty, and a pre-agricultural hunter-gatherer population from the Aleutian Islands (Murphy et al, 2003;Abdelfattah et al, 2013;Kim et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, this condition has been the subject of investigation in mummified remains. In particular, to assess whether atherosclerosis was a condition dependent on the lifestyle of Egyptian elites or if it was also encountered in ancient populations with different subsistence strategies (Allam et al, 2009(Allam et al, , 2011Thompson et al, 2013). Studies have demonstrated atherosclerosis in other prehistoric and historic mummies, including the chalcolithic Iceman, a mummy from the Joseon dynasty, and a pre-agricultural hunter-gatherer population from the Aleutian Islands (Murphy et al, 2003;Abdelfattah et al, 2013;Kim et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Diameter and blood velocity recordings resumed prior to cuff deflation and continued for 5 min for SFA and 3 min for the BA after deflation. Ultrasound images were continuously recorded at 5 frames·s −1 with Camtasia (TechSmith, Okemos, Mich., USA), and stored as .avi files [5,8]. This procedure was repeated hourly across the sitting intervals.…”
Section: Sfa and Ba Fmdmentioning
confidence: 99%
“…Arterial diameters and blood velocities: Off-line analysis of diameters were performed using automated edgedetection software (Brachial Analyzer, Medical Imaging Applications LLC, Coralville, IA, USA) as previously described [8,9]. This software allows the technician to determine a region of interest where the near and far vessel walls are most clear.…”
Section: Sfa and Ba Fmdmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from post mortem studies demonstrated the presence of atheromatous lesions in coronary arteries in children (Stary 2000). It is often thought of as a disease associated with a modern sedentary lifestyle and a lipid abundant diet Recently Allam and colleagues (Allam et al 2011) have imaged fifty two ancient Egyptian mummies using multi slice computer tomography and identified atherosclerotic lesions (arterial wall calcification) in 45% of cases with calcification sites located in the aorta, coronary carotid, iliac and femoral arteries as well as in peripheral arteries.…”
Section: Introductionmentioning
confidence: 99%